Plan estratégico para el desarrollo comunitario en la lotización la florida, de la parroquia San Cristobal del cantón Quevedo periodo 2015 – 2019 - Holguín Pinto, Virginia Eugenia (2016)
This research work is aimed at identifying the unmet needs that the Allotment Florida, entering the socio economic situation of the people, meet the conditions of roads and mobility, connectivity and production processes of its economy is based. Through a situational analysis you will access the knowledge of reality, with the main source of information to people living in the sector through survey instruments and direct observation to provide real sector data and its people. The purpose of the study is to develop a strategic plan for local development, the same will become a tool for the industry through allowing their leaders put in place the management of the objectives outlined in the proposal through the liaison with relevant agencies such as the Decentralized Autonomous Municipal Government Quevedo Canton, the Provincial Government of Rivers, the provincial directorates of different ministries and state institutions in the framework of its powers. The diagnosis rose on the factors: economic partner, utilities, transportation and mobility, and connectivity. Thereby has a central idea of the most important needs facing the sector by building SWOT technique, the rate of potential and vulnerability of the sector was assessed. The proposed vision and mission as well as sixteen six strategic objectives and strategic lines of action that address the identified weaknesses and reality with the diagnosis of the factors studied in the sector arise.